Influence Technique Training Data sensor (Triton Wear) To improve biomechanical variables for some stages Performance and achievement 50m freestyle youth - Alfadly, Yousif Sareeh; Thamer , Ahmed (Journal of Physical Education, 2023)
Swimming is one of the sports with great muscular effort and complex motor performance that requires coordination and harmony between the movements of the parts of the body contributing to performance that defies the limits of humans. The development of physical abilities and the improvement of technical performance can only be separated from the support of scientific theories and technology, in order to improve training methods and feedback system based on the fusion of information and data using modern sensors and information collection system. On the performance and mechanical conditions of the swimmer to help develop performance and achievement, the researchers used for this purpose a device (Triton Wear data sensor) to collect information and feedback on performance, to prepare special exercises and correct thereal-time performance of 50 m swimmers. The research was conducted on a sample of swimmers amounting to (6) young swimmers whose technical and mechanical data was extracted after wearing the sensor under the head cover of each swimmer, and the performance data was analyzed on this system, and the experiment lasted for six weeks, during which special exercises and feedback were given. Instantaneous based on the sensor data of each member of the sample, and after conducting post-tests, it was shown that the exercises and feedback based on the sensor technology, had a direct impact on  the improvement of the average performance  of the sample in the  50-meter freestyle   race and the improvement of all biomechanical values (such as average speed, frequency and length, acceleration and instantaneous strength) This improvement indicated that data collection and nutrition  Using the sensor's multi-information  fusion  can be  applied more precisely and differently in the  training of different swimming races, and can find many motor problems in sports swimmers to describe training solutions for them, both for specific parts of the body and the body as a whole. Techniques for accurately identifying this valuable information can therefore be used for quantitative biomechanical analysis. And to reach the training process.